Rare case of aortic aneurysm with type A dissection (extending to right coronary artery) and severe AR in a nonhypertensive and non pregnant female. (2019) - H.S., Natraj Setty; Chikamuniswamy, Rama; M.C., Yeriswamy; Patil, Rahul; Patil, Veeresh; Raj, Sathwik; Jadav, Santhosh; D., Balraju; B.N., Krishna Murthy; Reddy, Babu; B.C., Srinivas; T.R., Raghu; et al.
Highlights: Aortic dissection has a high mortality rate. It is common in elderly males. Aortic dilatation definitely increases risk but is not a must in every case. Clinical manifestation of Aortic dissection can be variable, therefore its diagnosis is challenging. Primary suspicion of Aortic dissection is usually based on a patient's history which varies from typical complaints like a sharp, severe tearing kind of backache with chest pain to asymptomatic until associated with valvular regurgitation. Consequent treatment with antiplatelet, antithrombin and thrombolytic agents can cause life-threatening to bleed. Apart from good blood pressure control, prevention of aortic dissection can be done by elective aortic surgery in patients with dilated ascending aorta. The most important and common risk factor is the systemic hypertension which has been reported in the 70% of the patients with aortic dissection. Most of the aortic dissection observed in young women has been reported to be related to pregnancy. Abstract: Introduction: Typically a patient with acute aortic dissection presents with severe chest pain radiating to the back, tearing in nature. Rarely it can present as painless acute aortic dissection this is seen in iatrogenic cases or when associated with atherosclerosis, diabetes, or aortic aneurysm. Case presentation: We hereby present a case of a 32-year aged female who presented with dyspnoea & palpitations (NYHA III) from last 6 months, diagnosed to have Aortic Aneurysm with Type A dissection & Severe AR. She eventually underwent BENTALL'S procedure with CABG and had an uneventful recovery. Discussion: Clinical manifestation of Aortic dissection can be variable, therefore its diagnosis is challenging. 25% of cases, may have associated ECG changes suggestive of acute coronary syndrome leading to a possible misdiagnosis especially if associated ST elevation in ECG. Aorto arteritis is a non-atherosclerotic chronic inflammatory vascular disease of unknown etiology that affects the aorta, proximal parts of its major branches. In this case, there is a possibility that there was underlying spontaneous coronary artery dissection which in turn could be cause for silent ischemia in young women. Conclusion: Acute aortic dissection is a life-threatening disease with a high rate of cardiovascular morbidity and mortality. The most important and common risk factor is systemic hypertension which has been reported in the 70% of the patients with aortic dissection. Most of the aortic dissection observed in young women has been reported to be related to pregnancy. Dissection should be suspected during any acute coronary syndrome, particularly Inferior wall MI.